Method for preparing oriented alumina fiber toughened ceramic by using supergravity
The supergravity centrifugal guidance method for alumina fiber-reinforced zirconia ceramics addresses the complexity and cost issues of existing methods, achieving enhanced fracture toughness and structural strength through directional fiber arrangement and additive enhancement.
Patent Information
- Application Number
- CN202411261993.8
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-09-10
- Publication Date
- 2024-12-13
AI Technical Summary
Existing fiber toughening methods for ceramics, particularly zirconia, are complex and costly, making them unsuitable for mass production, and there is a lack of effective methods for directional fiber arrangement to enhance fracture toughness.
A method involving the use of alumina fibers reinforced zirconia ceramics through a supergravity centrifugal guidance process, where alumina fibers are mixed with zirconia powder and additives, followed by ultra-gravity centrifugal treatment to achieve directional arrangement, enhancing the fracture toughness of zirconia ceramics.
The method results in alumina fiber-reinforced zirconia ceramics with improved fracture toughness, low production costs, and ease of industrialization, utilizing additives like lanthanum niobate and barium titanate to enhance structural strength and reduce porosity, resulting in a densified and toughened ceramic product.
Smart Images

Figure CN119118691A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of high-performance ceramics, and in particular to a method for preparing alumina fiber reinforced zirconia ceramics. Background Art
[0002] Compared with engineering metals, ceramic materials have the characteristics of high hardness, good wear resistance, high high temperature strength, good chemical stability, strong resistance to acid, alkali, salt and other media corrosion, and excellent insulation performance. Therefore, ceramics have a wide range of uses in modern science and technology and industry. However, ceramic materials are generally brittle, and the intuitive manifestation is that under external load, the fracture is sudden and without warning; the indirect manifestation is that the mechanical impact resistance and temperature shock resistance are poor. From the microstructural point of view, the root of brittleness lies in the existence of microcracks, which easily cause high stress concentration, and then the microcracks expand and break. This greatly limits the application of ceramics in fasteners that require high toughness and some biomaterials.
[0003] Fiber toughening has become a common method for improving the brittleness of ceramics at home and abroad. For example, in patent CN114163251A, YAG nanofibers and ceramic powders are uniformly mixed to form a ceramic mixed matrix, sieved and granulated, and the mixed matrix is supersonic sprayed to prepare a nanofiber toughened ceramic coating; in patent CN115180968A, mullite fibers are soaked and modified to improve the toughness of mullite fibers, and the modified mullite fibers are pre-laid on alumina ceramics to form an effective toughening whole, so that after the alumina ceramics are fired, the overall toughness is greatly enhanced. At present, fiber directional arrangement for toughening has become a new method for fiber toughening. For example, in patent CN114988900A, whiskers and ceramic powders are uniformly mixed to form a ceramic mixed powder and pressed into a ceramic body, an electric field is applied to the ceramic body for flash burning and oscillating pressure is applied, and dynamic force-assisted flash forging sintering is performed to enhance the strength and fracture toughness of zirconia ceramics. The advantage of this fiber directional arrangement is that for the part that bears the bending strength in a specific direction, the direction of the fiber directional distribution is perpendicular to the direction of the breaking force, which will greatly improve the fracture toughness of the material in a specific direction. For example, the use of whiskers to reinforce zirconia implants in the manufacture of artificial dentures can improve the strength and fracture toughness of ceramic implants, taking into account biocompatibility, biological activity and aesthetic performance. Patent CN112516381A uses whiskers and uses whisker dispersion and polarization processes to prepare whisker-doped zirconia slurry. Through pulsed electric field-guided 3D-colloidal molding technology including normal pressure and high pressure layered grouting, a blank embryo with whisker gradient structure, directional and mesh-dispersed reinforcement of zirconia implants is prepared, and further prepared into high-strength and high-toughness whisker-reinforced zirconia implants. Existing fiber toughening methods mainly include electrophoresis, strong magnetic field method, etc., but these methods have complex preparation processes and difficult to control costs, which are not conducive to mass production. The present invention provides a method for supergravity fiber directional arrangement, which reduces production costs, significantly improves fiber orientation effects, and further enhances ceramic toughness.
[0004] Zirconia ceramic material is one of the most widely used ceramic materials. Because of its high strength, excellent wear resistance and good chemical stability and many other excellent properties, it has become the mainstream material for preparing all-ceramic denture restorations and ceramic fasteners and other daily-use ceramics. Doping fibers in zirconia can significantly enhance the fracture toughness of zirconia. For example, patent CN113845367A provides a high-temperature oxidation-resistant carbon fiber toughened zirconia ceramic material, including zirconium oxide and zirconium tungstate, and modified carbon fibers dispersed inside the zirconia. This zirconia ceramic material is toughened by carbon fibers of graphene oxide layers, aluminum oxide layers, and zirconium oxide layers coated sequentially from the inside to the outside. The multi-layer protective structure greatly improves the oxidation resistance of the carbon fibers, thereby greatly improving the toughness of the zirconia ceramic material. However, the method of fiber orientation has not been involved in various studies on fiber-toughened zirconia. The present invention provides a method for directional arrangement of aluminum oxide fibers in zirconia ceramics using a supergravity method to toughen zirconia ceramics. The product prepared by this method has excellent fracture toughness, low cost, and is easy to industrialize and produce, and belongs to an environmentally friendly technology. Summary of the invention
[0005] The object of the present invention is to provide a method for preparing oriented alumina fiber reinforced zirconia ceramics by utilizing supergravity, so as to solve the problems existing in the prior art.
[0006] In order to solve the above technical problems, the present invention provides the following technical solutions: an alumina fiber reinforced zirconia ceramic and a preparation method thereof, wherein the alumina fiber reinforced zirconia ceramic is prepared by mixing zirconia powder with alumina fibers, and with the assistance of additives, undergoing ultra-gravity centrifugal guiding treatment so that the alumina fibers are arranged in a directional manner in at least one spatial dimension.
[0007] Furthermore, the alumina fiber is an α-crystalline alumina whisker obtained by sintering aluminum nitrate nonahydrate and urea, and the mass percentage of the alumina fiber is 1-10% of the zirconium oxide powder.
[0008] Furthermore, a method for preparing alumina fiber reinforced zirconia ceramics comprises the following preparation steps:
[0009] (1) mixing zirconium oxide powder, alumina fiber, additives and deionized water to prepare a uniform ceramic slurry;
[0010] (2) separating the solid phase of the ceramic slurry under high gravity conditions to obtain a zirconia ceramic green body;
[0011] (3) The zirconia ceramic green body is dried at 40-105° C., and then sintered at 1350-1550° C. and kept warm for 0.5-2 h to obtain alumina fiber-reinforced zirconia ceramics.
[0012] Furthermore, the zirconium oxide powder in step (1) contains a stabilizer, lanthanum niobate, barium titanate and zirconium oxide.
[0013] Furthermore, the stabilizer includes at least one of yttrium oxide and cerium oxide, and the mass percentage of the stabilizer in the zirconium oxide is 2.5-12%.
[0014] Furthermore, the preparation method of the lanthanum niobate is: lanthanum oxide and niobium pentoxide are mixed in a molar ratio of 1:1, ground with a variable frequency planetary ball mill, using an alumina grinding jar and alumina ball milling balls, alcohol dispersant, a ball-to-material ratio of 3:1, a ball mill speed of 200r / min, after mixing for 24 hours, drying at 60°C, taking out and crushing, sieving with 125 mesh, calcining at 1000°C for 2 hours, and drying and sieving again to obtain lanthanum niobate.
[0015] Furthermore, the preparation method of the alumina fiber in step (1) is: mixing aluminum nitrate nonahydrate and urea in a molar ratio of 1:5, adding deionized water with a mass of 0.8 to 1.2 times that of the urea, stirring at 100 to 300 rpm for 30 min, preparing by hydrothermal method at 120°C for 24 h, and filtering, washing with ethanol and distilled water for 2 to 4 times respectively to obtain a precursor solid, and then sintering at 1350°C and keeping warm for 240 min to obtain alumina fiber.
[0016] Furthermore, the additive in step (1) is at least three of nitric acid, acetic acid, citric acid, polyacrylic acid, polyethylene glycol, polyvinyl alcohol, polyglycerol, polypropylene, and polyethylene, and the mass percentage of the additive is 1 to 3% of the sum of the mass of the zirconium oxide powder and the alumina fiber.
[0017] Furthermore, the volume percentage of the deionized water in step (1) is 80-150% of the zirconium oxide powder.
[0018] Furthermore, the supergravity condition in step (2) is as follows: the gravity coefficient ranges from 2000 to 8000 g, where g is the acceleration of gravity, and the molding time is 10 to 30 minutes.
[0019] Compared with the prior art, the beneficial effects achieved by the present invention are:
[0020] The invention is prepared by mixing zirconium oxide powder with alumina fiber and, with the aid of additives, undergoing ultra-gravity centrifugal guiding treatment to achieve the effect of toughening ceramics.
[0021] Firstly, the present invention utilizes doped cerium ions and yttrium ions to occupy the position of zirconium ions to form a substitutional solid solution, generates point defects inside zirconia, increases the chemical barrier for the transformation from tetragonal phase to monoclinic phase, enhances stability, prevents crystal transformation, and indirectly improves the fracture toughness of the material; then, lanthanum niobate is uniformly dispersed in zirconia to improve the structural strength of the ceramic, thereby allowing the matrix to have ferroelasticity caused by reversible domain structure switching, and when the lanthanum niobate phase appears at the front end of the extended crack, the stress concentration there will stimulate the internal domain switching and generate corresponding strain, so that the stress at the front end of the crack is relaxed, thereby hindering the crack from expanding, and greatly improving the toughness of the ceramic; then, the addition of barium titanate can also hinder the expansion of the crack, and in the subsequent sintering step, it can reduce the porosity of the material, effectively avoid stress concentration around the pores, thereby improving the fracture toughness, bending strength and Vickers hardness of the sintered body, and play a certain strengthening role on the ceramic material.
[0022] Secondly, the present invention utilizes aluminum nitrate nonahydrate and urea to sinter to generate α-crystalline aluminum oxide whiskers, and uses whisker dispersion and polarization processes to prepare whisker-doped zirconia slurry, and prepares a whisker structure with a directional arrangement in at least one spatial dimension by a method of ultra-gravity centrifugal guidance, and further processes to form a product, and promotes the directional arrangement of whiskers at high temperature by using additives, eliminates pores and gaps to achieve complete densification of the matrix, and prepares alumina fiber-reinforced zirconia ceramics; and the ultra-gravity centrifugal guidance makes the direction of the directional distribution of the whiskers perpendicular to the direction of the breaking force, and It has a doping gradient structure, which greatly improves the fracture toughness of the material in a specific direction. Then, during sintering, the pores and gaps in the matrix are eliminated, and the lanthanum niobate promotes the growth of matrix grains, thereby enhancing the density of whisker sintering. Under the action of external force, stress concentration occurs near cracks and defects in the matrix. When the concentrated stress reaches the coercive stress of lanthanum niobate, lanthanum niobate undergoes domain switching response, absorbs energy during the switching process, reduces the elastic strain energy of the matrix, and reduces the stress field intensity at the crack tip, thereby achieving the effect of improving the toughening of the ceramic material. BRIEF DESCRIPTION OF THE DRAWINGS
[0023] The accompanying drawings are used to provide a further understanding of the present invention and constitute a part of the specification. Together with the embodiments of the present invention, they are used to explain the present invention and do not constitute a limitation of the present invention. In the accompanying drawings:
[0024] Figure 1 Schematic diagram of the directional distribution of aluminum oxide whiskers in zirconium oxide ceramics;
[0025] Figure 2 This is a schematic diagram of the ultra-gravity centrifugal orientation method;
[0026] Figure 3 Schematic diagram of the process for preparing alumina whisker toughened zirconia ceramics. DETAILED DESCRIPTION
[0027] The following will be combined with the embodiments of the present invention to clearly and completely describe the technical solutions in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without making creative work are within the scope of protection of the present invention.
[0028] In order to more clearly illustrate the method provided by the present invention, the following examples are used to describe in detail the various index testing methods of the alumina fiber reinforced zirconia ceramics prepared in the following examples are as follows:
[0029] The three-point bending method was used to measure the bending strength on a CMT4304 microcomputer-controlled electronic universal material testing machine, and the preliminary surface morphology was recorded. The density test was carried out according to the Archimedean principle and the provisions of GB / T5586.2998. The transverse fracture toughness was tested by using the indentation and crack length produced by the fully automatic microhardness tester KB30S-FA.
[0030] Example 1
[0031] (1) Aluminum nitrate nonahydrate and urea were mixed in a molar ratio of 1:5, deionized water of 1 times the mass of urea was added, stirred at 200 rpm for 30 min, hydrothermally prepared at 120° C. for 24 h, filtered, washed with ethanol and distilled water for 3 times respectively to obtain a precursor solid, and then sintered at 1350° C. and kept warm for 240 min to obtain alumina fiber; zirconium oxide powder, alumina fiber, additives and deionized water were mixed to prepare a uniform ceramic slurry; the additives were dispersant polyethylene glycol, lubricant polyglycerol and binder polyethylene, and the specific amounts of each raw material were shown in Tables 1 and 2;
[0032] (2) injecting the ceramic slurry into a centrifugal mold and molding it under a condition of a supergravity coefficient of 8000g for 10 minutes to obtain a zirconia ceramic green body, so that the aluminum oxide whiskers are oriented in at least one dimension in the zirconia ceramic green body;
[0033] (3) The zirconia ceramic green body was dried at 70° C., then sintered and kept warm for 1 hour to obtain alumina fiber-reinforced zirconia ceramics.
[0034] Example 2
[0035] (1) Aluminum nitrate nonahydrate and urea were mixed in a molar ratio of 1:5, deionized water of 1 times the mass of urea was added, stirred at 200 rpm for 30 min, hydrothermally prepared at 120° C. for 24 h, filtered, washed with ethanol and distilled water for 3 times respectively to obtain a precursor solid, and then sintered at 1350° C. and kept warm for 240 min to obtain alumina fiber; zirconium oxide powder, alumina fiber, additives and deionized water were mixed to prepare a uniform ceramic slurry; the additives were dispersant polypropylene alcohol, lubricant polyamide and binder polyethylene, and the specific amounts of each raw material were shown in Tables 1 and 2;
[0036] (2) injecting the ceramic slurry into a centrifugal mold and molding it under a condition of a supergravity coefficient of 8000g for 10 minutes to obtain a zirconia ceramic green body, so that the aluminum oxide whiskers are oriented in at least one dimension in the zirconia ceramic green body;
[0037] (3) The zirconia ceramic green body was dried at 70° C., then sintered and kept warm for 1 hour to obtain alumina fiber-reinforced zirconia ceramics.
[0038] Comparative Example 1
[0039] (1) Aluminum nitrate nonahydrate and urea were mixed in a molar ratio of 1:5, deionized water 0.8 times the mass of urea was added, stirred at 100 rpm for 30 min, hydrothermally prepared at 120° C. for 24 h, filtered, washed twice with ethanol and distilled water respectively to obtain a precursor solid, and then sintered at 1350° C. and kept warm for 240 min to obtain alumina fiber; zirconium oxide powder, alumina fiber, additives and deionized water were mixed to prepare a uniform ceramic slurry; the additives were dispersant polypropylene alcohol, lubricant polyamide and binder polypropylene, and the specific amounts of each raw material were shown in Tables 1 and 2;
[0040] (2) injecting the ceramic slurry into a centrifugal mold and molding it under a condition of a supergravity coefficient of 4000g for 15 minutes to obtain a zirconia ceramic green body, so that the aluminum oxide whiskers are oriented in at least one dimension in the zirconia ceramic green body;
[0041] (3) The zirconia ceramic green body was dried at 40° C., and then sintered and kept warm for 0.5 h to obtain alumina fiber-reinforced zirconia ceramics.
[0042] Comparative Example 2
[0043] (1) Aluminum nitrate nonahydrate and urea were mixed in a molar ratio of 1:5, deionized water of 0.8 times the mass of urea was added, stirred at 100 rpm for 30 min, hydrothermally prepared at 120° C. for 24 h, filtered, washed twice with ethanol and distilled water respectively, to obtain a precursor solid, and then sintered at 1350° C. and kept warm for 240 min to obtain alumina fiber; zirconium oxide powder, alumina fiber, additives and deionized water were mixed to prepare a uniform ceramic slurry; the additives were dispersant polyethylene glycol, lubricant polyamide and binder polyethylene, and the specific amounts of each raw material were shown in Tables 1 and 2;
[0044] (2) injecting the ceramic slurry into a centrifugal mold and molding it under a condition of a supergravity coefficient of 5000g for 20 minutes to obtain a zirconia ceramic green body, so that the aluminum oxide whiskers are oriented in at least one dimension in the zirconia ceramic green body;
[0045] (3) The zirconia ceramic green body was dried at 40° C., and then sintered and kept warm for 0.5 h to obtain alumina fiber-reinforced zirconia ceramics.
[0046] Comparative Example 3
[0047] (1) Aluminum nitrate nonahydrate and urea were mixed in a molar ratio of 1:5, deionized water 1.2 times the mass of urea was added, stirred at 300 rpm for 30 min, hydrothermally prepared at 120° C. for 24 h, filtered, washed with ethanol and distilled water 4 times each to obtain a precursor solid, and then sintered at 1350° C. and kept warm for 240 min to obtain alumina fiber; zirconium oxide powder, alumina fiber, additives and deionized water were mixed to prepare a uniform ceramic slurry; the additives were dispersant polypropylene alcohol, lubricant polyglycerol and binder polypropylene. The specific amounts of each raw material are shown in Tables 1 and 2;
[0048] (2) injecting the ceramic slurry into a centrifugal mold and molding it under a condition of a supergravity coefficient of 12000g for 30 minutes to obtain a zirconia ceramic green body, so that the aluminum oxide whiskers are oriented in at least one dimension in the zirconia ceramic green body;
[0049] (3) The zirconia ceramic green body was dried at 105°C, then sintered and kept warm for 2 hours to obtain alumina fiber-reinforced zirconia ceramics.
[0050] Comparative Example 4
[0051] (1) Aluminum nitrate nonahydrate and urea were mixed in a molar ratio of 1:5, deionized water 1.2 times the mass of urea was added, stirred at 300 rpm for 30 min, hydrothermally prepared at 120° C. for 24 h, filtered, washed with ethanol and distilled water 4 times each to obtain a precursor solid, and then sintered at 1350° C. and kept warm for 240 min to obtain alumina fiber; zirconium oxide powder, alumina fiber, additives and deionized water were mixed to prepare a uniform ceramic slurry; the additives were dispersant polyethylene glycol, lubricant polyamide and binder polypropylene, and the specific amounts of each raw material were shown in Tables 1 and 2;
[0052] (2) injecting the ceramic slurry into a centrifugal mold and molding it under a condition of a supergravity coefficient of 13000g for 22 minutes to obtain a zirconia ceramic green body, so that the aluminum oxide whiskers are oriented in at least one dimension in the zirconia ceramic green body;
[0053] (3) The zirconia ceramic green body was dried at 105°C, then sintered and kept warm for 2 hours to obtain alumina fiber-reinforced zirconia ceramics.
[0054] Table 1
[0055]
[0056] Table 2
[0057] additive Composition and mass ratio of additives Example 1 Polyethylene glycol 0.1wt%, polyglycerol 0.2wt%, polyethylene 0.35wt% Example 2 Polypropylene alcohol 0.5wt%, polyamide 1.0wt%, polyethylene 0.5wt% Comparative Example 1 Polypropylene alcohol 1.0wt%, polyamide 1.1wt%, polypropylene 0.24wt% Comparative Example 2 Polyethylene glycol 1.25wt%, polyamide 1.5wt%, polyethylene 0.56wt% Comparative Example 3 Polypropylene alcohol 0.9wt%, polyglycerol 1.5wt%, polypropylene 0.4wt% Comparative Example 4 Polyethylene glycol 0.7wt%, polyamide 1.4wt%, polypropylene 0.3wt%
[0058] Table 3
[0059] Bending strength(MPa) <![CDATA[Transverse fracture toughness (MPa·m 1 / 2 )]]> Density(%) Surface morphology Example 1 475 4.96 98.43 No cracks Example 2 492 517 99.05 No cracks Comparative Example 1 418 4.04 90.72 Many cracks Comparative Example 2 421 431 92.51 Many cracks Comparative Example 3 452 4.82 95.97 A few cracks Comparative Example 4 443 4.85 96.38 A few cracks
[0060] From the data comparison of the embodiments and the comparative examples in Table 1, Table 2 and Table 3, it can be found that if the content of the aluminum oxide whiskers of the present invention is too low, the toughening effect is not good, and if the content is too high, the sintered body is not easy to be densified and sintered; the additive is used to promote the directional distribution of the aluminum oxide whiskers in the zirconia ceramic, wherein the dispersion effect is poor if the amount of dispersant is low, but the discharge is difficult if the amount is too high, the drying process is long, and it is easy to crack; if the lubricant content is too low, the lubrication effect is poor, which affects the dispersion effect of the product whiskers, and if the amount is too high, the debinding is difficult; if the amount of the binder is low, cracking will occur during sintering, and if the amount is high, the debinding process will be greatly affected, and the density of the product after sintering will be irreversibly affected; if the amount of deionized water added is too low, it is not conducive to the dispersion of the whiskers in the powder, but if the amount is too high, the product density will be reduced and the production cost will increase; under too low gravity acceleration, the dispersion effect of the aluminum oxide whiskers in the zirconia ceramics will be poor, the whiskers will be difficult to orient, and too high gravity acceleration will cause energy waste.
[0061] It will be apparent to those skilled in the art that the invention is not limited to the details of the exemplary embodiments described above and that the invention can be implemented in other specific forms without departing from the spirit or essential features of the invention. Therefore, the embodiments should be considered in all respects as exemplary and non-limiting, and the scope of the invention is defined by the appended claims rather than the foregoing description, and it is intended that all variations within the meaning and scope of the equivalent elements of the claims be included in the invention. Any marking in a claim should not be considered as limiting the claim to which it relates.
Claims
1. A method for preparing alumina fiber reinforced zirconia ceramics, characterized in that: The alumina fiber reinforced zirconia ceramic is prepared by mixing zirconium oxide powder with alumina fibers, and with the aid of additives, undergoing ultra-gravity centrifugal guiding treatment to allow the alumina fibers to be arranged in a directional manner in at least one spatial dimension.
2. The method for preparing an alumina fiber reinforced zirconia ceramic according to claim 1, characterized in that: The alumina fiber is an alpha-crystal alumina whisker, which is obtained by sintering aluminum nitrate nonahydrate and urea. The mass percentage of the alumina fiber is 1-10% of the zirconium oxide powder.
3. The method for preparing alumina fiber reinforced zirconia ceramics according to claim 1, characterized in that: The method comprises the following preparation steps: (1) mixing zirconium oxide powder, alumina fiber, additives and deionized water to prepare a uniform ceramic slurry; (2) separating the solid phase of the ceramic slurry under high gravity conditions to obtain a zirconia ceramic green body; (3) The zirconia ceramic green body is dried at 40-105° C., and then sintered at 1350-1550° C. and kept warm for 0.5-2 h to obtain alumina fiber-reinforced zirconia ceramics.
4. The method for preparing alumina fiber reinforced zirconia ceramics according to claim 3, characterized in that: The zirconium oxide powder in step (1) contains a stabilizer, lanthanum niobate, barium titanate and zirconium oxide.
5. The method for preparing alumina fiber reinforced zirconia ceramics according to claim 4, characterized in that: The stabilizer includes at least one of yttrium oxide and cerium oxide, and the mass percentage of the stabilizer in the zirconium oxide is 2.5-12%.
6. The method for preparing alumina fiber reinforced zirconia ceramics according to claim 4, characterized in that: The preparation method of the lanthanum niobate is as follows: lanthanum oxide and niobium pentoxide are mixed in a molar ratio of 1:1, ground with a variable frequency planetary ball mill, an alumina grinding jar and alumina ball milling balls, an alcohol dispersant, a ball-to-material ratio of 3:1, a ball milling speed of 200 r / min, mixed for 24 hours, dried at 60° C., taken out and crushed, sieved with 125 mesh, calcined at 1000° C. for 2 hours, dried and sieved again, to obtain lanthanum niobate.
7. The method for preparing alumina fiber reinforced zirconia ceramics according to claim 3, characterized in that: The preparation method of the alumina fiber described in step (1) is as follows: aluminum nitrate nonahydrate and urea are mixed in a molar ratio of 1:5, deionized water is added in an amount of 0.8 to 1.2 times the mass of urea, and the mixture is stirred at 100 to 300 rpm for 30 min. The mixture is prepared by a hydrothermal method at 120°C for 24 h, and filtered. The mixture is washed with ethanol and distilled water for 2 to 4 times respectively to obtain a precursor solid. The solid is then sintered at 1350°C and kept warm for 240 min to obtain alumina fiber.
8. The method for preparing alumina fiber reinforced zirconia ceramics according to claim 3, characterized in that: The additive in step (1) is at least three of nitric acid, acetic acid, citric acid, polyacrylic acid, polyethylene glycol, polyvinyl alcohol, polyglycerol, polypropylene, and polyethylene, and the mass percentage of the additive is 1 to 3% of the sum of the mass of zirconium oxide powder and alumina fiber.
9. The method for preparing alumina fiber reinforced zirconia ceramics according to claim 3, characterized in that: The volume percentage of the deionized water in step (1) is 80-150% of the zirconium oxide powder.
10. The method for preparing alumina fiber reinforced zirconia ceramics according to claim 3, characterized in that: The supergravity conditions in step (2) are: the gravity coefficient ranges from 2000 to 8000g, where g is the acceleration of gravity, and the molding time is 10 to 30 minutes.
Citation Information
Patent Citations
Whisker reinforced zirconium oxide implant
CN112516381A
Preparation method of high-temperature antioxidant carbon fiber toughened zirconia ceramic material and high-temperature antioxidant carbon fiber toughened zirconia ceramic material
CN113845367A
Nanofiber toughened silicon carbide surface environment barrier ceramic coating and preparation method thereof
CN114163251A
Method for preparing whisker toughened ceramic matrix composite material by dynamic pressure flash firing
CN114988900A
Novel fiber toughened alumina ceramic and preparation method thereof
CN115180968A
Cited By
Porous toughened ceramic and preparation method thereof
CN120554140A
A porous toughened ceramic and a method of making the same
CN120554140B
Yttria-stabilized zirconia ceramic containing nanofiber alumina and preparation method thereof
CN120794614A
